2021
DOI: 10.1002/lno.11773
|View full text |Cite
|
Sign up to set email alerts
|

Food web structure in relation to environmental drivers across a continental shelf ecosystem

Abstract: Quantification of the physical and biological factors that influence the spatial structuring of food webs is central to inform effective resource management. We used baseline-corrected stable isotope ratios (δ 13 C and δ 15 N) of 63 invertebrate and fish to investigate food web structure across a continental shelf gradient-the Celtic Sea Shelf in the Northeast Atlantic Ocean. Hierarchical clustering on δ 13 C and δ 15 N showed that the shelf food web is characterized by four trophic levels with trophic groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The classical ecological theory (Macarthur and Levins 1967) predicts that a high overlap of the feeding niche between species will lead to an increase in competition, which would result in either ecological differentiation or local extinction. It was shown that in communities with high feeding niche overlap dominant species tend to maximize the resource use through higher feeding plasticity (Lesser et al 2020; Walters et al 2021). Similarly, higher FEve at deeper sites both at the open coast and in the river vicinity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The classical ecological theory (Macarthur and Levins 1967) predicts that a high overlap of the feeding niche between species will lead to an increase in competition, which would result in either ecological differentiation or local extinction. It was shown that in communities with high feeding niche overlap dominant species tend to maximize the resource use through higher feeding plasticity (Lesser et al 2020; Walters et al 2021). Similarly, higher FEve at deeper sites both at the open coast and in the river vicinity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the environmental diversity characterizing the Celtic Sea (Hernvann et al, 2020; Walters et al, 2021), the generalist feeding behavior and ontogenetic diet shifts of some species (Day et al, 2019; Issac et al, 2017; Rault et al, 2017), the functional redundancy of several groups (Mérillet et al, unpublished manuscript), and benthic–pelagic coupling (Hernvann et al, 2020), data exhibited high intragroup variability and among‐group overlap in isotope signatures. Therefore, posterior distributions of dietary proportions were often diffuse, pointing out the limits of bulk SIA for studying such complex ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The choices of appropriate baseline species and Trophic Enrichment Factors (TEF hereafter) were key steps in ensuring robust trophic position estimations [52]. Suspension feeding bivalves have long been recognized as reliable baseline references in studies of freshwater [53,54] and, more recently, marine food webs [55,56], since they have a relatively long biological cycle, a low metabolic rate, and are able to integrate highly variable isotope values among primary producers [53,57]. Here we used the cumulated δ 13 C and δ 15 N values of the two suspensivore bivalves Modiolus barbatus and Pinctada radiata as baseline, assuming a trophic level λ = 2 after a PERMANOVA indicated negligible inter-specific differences (see Results).…”
Section: Discussionmentioning
confidence: 99%